1985
DOI: 10.1007/bf00571753
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cytotoxic activities of chemotherapeutic drugs using a human bladder cancer cell line

Abstract: Many chemotherapeutic drugs have been used to treat patients with advanced bladder cancer, but few of these have been evaluated adequately in phase II clinical trials. Continuous cell lines provide one means for comparing the in vitro cytotoxicities of anticancer agents. In this study, a continuous cell line derived from a transitional cell cancer of the human bladder, which still produces tumours histologically similar to the tumour of origin on xenotransplantation, was used to measure the in vitro cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The drug acts on neoplastic cells at phase G 0 , being able to interact not only with DNA but also with mRNA. In vitro studies on TCC of bladder cell lines, mitoxantrone was shown to be one of the most vigorous cytotoxic agents tested [36]. Intravesical mitoxantrone appears to hold promise as an effective chemoprophylactic compound.…”
Section: Mitoxantronementioning
confidence: 98%
“…The drug acts on neoplastic cells at phase G 0 , being able to interact not only with DNA but also with mRNA. In vitro studies on TCC of bladder cell lines, mitoxantrone was shown to be one of the most vigorous cytotoxic agents tested [36]. Intravesical mitoxantrone appears to hold promise as an effective chemoprophylactic compound.…”
Section: Mitoxantronementioning
confidence: 98%
“…Experience is limited with cytostatic mitoxantrone and the immunomodulator IFN·-2b. Mitoxantrone is known to exhibit a steep cytotoxic activity when compared with other chemotherapeutic drugs in vitro [9]. Also, bladder cancer cells are found to express more recombinant IFN·-2b receptors than do normal cells [10].…”
Section: Discussionmentioning
confidence: 93%
“…The continuous cell lines T24 and RT112 were both derived from transitional cell carcinomas of the human bladder and were grown as monolayers using conditions described elsewhere (Hepburn et al, 1985). The T24 cells were almost twice as sensitive (IC, 7.6pg/ml) as RT112 cells (ICw 14.4pg/ml) after a 1 h exposure to a cytotoxic range of concentrations of cisplatin.…”
Section: U Kmentioning
confidence: 99%